The Relationship of Knowledge of COVID-19 Vaccines and Implementation of Health Protocols Post COVID-19 Vaccination - Saraswati, Alya; Salvana Sekar Nucifera; Yusril Hidayat; Devitasari; Ariesta Yusuf; Kiki Antafa N; Maulidya Nur H; Namira Shalawasabila; Wynne Tara; Sherly Maidasari; Margareth Liu; Syafa Revita; Annisa Riski Azzahrani; Fatimah Rustika Putri; Gesnita Nugraheni (Universitas Airlangga, 2024)
The COVID-19 pandemic has caused fatalities and brought significant impact on various fields. The vaccine was an important effort to overcome the COVID-19 pandemic. Low knowledge regarding the effectiveness of the COVID-19 vaccine and the Peltzman Effect has the potential to be a cause of ignorance behavior to health protocols. This study was conducted to find out the public's knowledge about the COVID-19 vaccine and the implementation of public health protocols after COVID-19 vaccination. Differences in application before and after vaccination were also studied. This study was a cross-sectional study with accidental sampling techniques. The survey was conducted online using a google form. The inclusion criteria in this study were respondents who were more than 18 years old, have been vaccinated for COVID-19 for at least first dose, domiciled in Java Island. The analysis was conducted using the Mann-Whitney U Test. The There were 456 participants in this study. The results showed that 306 respondents had high knowledge (67.1%), 141 respondents had moderate knowledge (30.9%), and 9 respondents had low knowledge (2.0%). Based on a correlation tests, it was found that there was a relationship between knowledge and public behavior in implementing health protocols (p<0.05). The behavior of implementing health protocols before vaccination was better than after vaccination (p<0.05). Respondents' knowledge of the COVID-19 vaccine significantly affected the behavior of implementing the respondent's health protocols. Health promotion that emphasizes the COVID-19 vaccine and the importance of still implementing post-vaccine health protocols needs to remain encouraged.